Dispersion Study of Zirconia Nano-Powders Using Dolapix CE64 and M65 Dispersant to Develop UF Membrane over Novel Clay-Alumina Based Ceramic Support for Water Treatment. Issue 4 (2nd October 2019) - Dey, Surajit; Roy, Somendra Nath; Majumdar, Swachchha; Ghosh, Sourja; Sahoo, Ganesh C.
ABSTRACT: Dispersion of zirconia powder in aqueous suspension using suitable dispersant for coating application was studied. Zeta potential experiments were conducted in search of stable suspensions. Sedimentation tests were carried out in both acidic and basic pH range, i.e. from 2 to 11. Zirconia slurry as coating material was used for coating on clay-alumina tubular ceramic support. The slurry was composed of zirconia nano powder, water, dispersant and organic binder. Z irconia nano powders were characterized by XRD, surface area by multipoint BET and TEM. The effect of dispersant concentration on zeta potential of zirconia suspension and effect of pH, sedimentation rate and rheology (viscosity) of zirconia suspension were studied. The coated tubes were air dried and sintered in furnace at 700°C for 2 h. The prepared UF membrane was subjected to characterization in terms of permeability, FESEM, molecular weight cut off, etc. The UF membrane was used for separation of two types of water – effluent A (kitchen sink wastewater) and effluent B (surface water of a lake). The membrane was effective to remove the pathogenic organisms, organic load in terms of BOD, COD, etc. The treated water may be reused in agriculture or industrial purposes. GRAPHICAL ABSTRACT: